Targeting Certain Interleukins as Novel Treatment Options for Liver Fibrosis - An, Su Yeon; Petrescu, Anca D.; DeMorrow, Sharon (Frontiers in Pharmacology, 2021)
The liver is a major metabolic organ and an immunologically complex organ. It produces and uses many substances such as acute phase proteins, cytokines, chemokines, and complementary components to maintain the balance between immunity and tolerance. Interleukins are important immune control cytokines, that are produced by many body cells. In liver injury, interleukins are produced in large amount by various cell types, and act as pro-inflammatory (e.g. interleukin (IL)-6, IL-13, IL-17, and IL-33) as well as anti-inflammatory (e.g. IL-10) functions in hepatic cells. Recently, interleukins are regarded as interesting therapeutic targets for the treatment of liver fibrosis patients. Hepatic cells such as hepatocytes, hepatic stellate cells, and hepatic macrophages are involved to the initiation, perpetuation, and resolution of fibrosis. The understanding of the role of interleukins in such cells provides opportunity for the development of therapeutic target drugs. This paper aims to understand the functional roles of interleukins in hepatic and immune cells when the liver is damaged, and suggests the possibility of interleukins as a new treatment target in liver fibrosis.